Multivalvular Disease: Percutaneous Management in 2019 and Beyond - Magdalena Erlebach (Radcliffe Medical Media, 2019)
Patients with multivalvular disease (MVD) are common and often present with heterogeneous valve defects. Evaluation is complicated by interactions among various valve pathologies. Trials and guidelines focus primarily on single-valve disease, providing few recommendations for the treatment of patients with MVD. This article provides an insight into percutaneous treatment possibilities for this heterogeneous patient population.